UNSAFE ABORTION BUSINESS, UNTIL WHEN? - ROSPITA ADELINA SIREGAR (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2020)
Pregnancy occurs and unwanted frequently bring a big issue for women, pregnancy backgrounds were varies, there is for having sex outside marriage, incest, or pregnancy due to the factor of sex crimes such as rape and others. For a pregnant woman in astate of not having a partner is certainly not easy to survive, therefore often thought to abort appears and choose the easiest way, which is not to the doctor because it will find a variety of procedures. Then choose to go to a clinic that serves the practice of illegal abortions, such as a police case reports in February 2020 that uncovered the practice of illegal abortions in a clinic in the area of Central Jakarta. In terms of the application of positive law in Indonesia, the problem was raised again, namely how the supervision and application of criminal law against illegal abortion business? When people are free to choose, the consequences will increase the maternal mortality rate itself. Should the birth of regulations governing therapeutic abortion, safe abortion will be the answer to the fate of women in the future.